The Power Game: Continued Reflections on the Early Development of Modern Football. Issue 3 (11th February 2016) - Curry, Graham; Dunning, Eric
Abstract: In this paper the authors seek to continue the debate on the development of modern football. They note the support offered by Tony Collins to the long-standing reservations of Graham Curry and Eric Dunning regarding the weaknesses of the revisionist case, which has sought to lessen the influence of public schoolboys on the game's early years. The authors do, however, offer some correctives to Collins's thoughts, particularly in terms of the complex Sheffield footballing subculture. Curry and Dunning support the need for more research based on local studies and attempt to gather together current thinking in this area.